Mental Strengthening through Character Education Management in Pencak Silat Extracurricular Program - Haedari, Amin; Samadi, Muhammad Iqbal Bin; Iskandar, Nur Muhammad; Bakhrudin, Muhammad (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
Moral decadence in society is at an alarming level, reaching 63%. Character education is an educational practice that fosters student char-acter. This study aims to develop character education with four pillars and strengthen the moral formation. The approach in this study uses qualitative methods, with a case study in which the author conducts ob-servations, interviews, and documentation. The use of primary data with the subject of the principal and secondary data with the subject Vice principal for curriculum, madrasa commit, Extracurricular teacher and using purposive sampling. Data were analyzed using four stages of Miles and Huberman and then tested, starting from credibility through triangulation, dependability and confirmability. The resulting study shows there are characteristics inside and outside of the school, inside exschool and outside, like discipline, courage, independence, responsi-bility, sportsmanship and mutual respect. When many characters adhere to the student consistently, indirectly, the student will become a good character and strengthen his mental. The implication of this research is that strong character will strengthen the mental of the student.